Depth Vs Breath in the arrangement of web links - Zaphiris, Panayiotis (My University, 2000)
The purpose of this study was to examine the effect of depth and breadth in the arrangement of web link hierarchies on the user preference, response time and errors. An experiment is reported, where previous menu depth/breath tradeoff procedures are applied to the web link domain. The variables evaluated were five different web page linking strategies with varying depth and breadth. The results indicate that task completion time increases as the depth of the web site structure increases.